2017
DOI: 10.5010/jpb.2017.44.1.061
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gibberellic Acid-Stimulated Arabidopsis (GASA) gene to drought stress response in Poplar (Populus alba × P. glandulosa)

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Abstract Gibberellic Acid-Stimulated Arabidopsis (GASA) genes are involved in plant hormone signaling, cell division and elongation, as well as in responses to stress conditions in plants. In this study, we isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…GASA influence various biological processes and signal transduction pathways, and then playing critical roles in plant growth and development (Choi et al, 2017). Due to complexities in functional mechanisms, different members of the GASA gene family have identical or diverse functions during the vegetative and reproductive stages.…”
Section: Discussionmentioning
confidence: 99%
“…GASA influence various biological processes and signal transduction pathways, and then playing critical roles in plant growth and development (Choi et al, 2017). Due to complexities in functional mechanisms, different members of the GASA gene family have identical or diverse functions during the vegetative and reproductive stages.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, we developed a shoot regeneration technology from the leaf and shoot derived calli of the hybrid poplar (Populus alba × P. glandulosa) (Choi et al, 2020) for the successful generation of transgenic plants using Agrobacterium-mediated transformation (Chung et al, 1989;Choi et al, 2005;Song et al, 2019). Using hybrid poplar, transgenic plants have been successfully generated with several different genes involved in a variety of physiological responses (Zhang et al, 2011;Shim et al, 2013;Choi et al, 2017;Yoon et al, 2018;Kim et al, 2020). Since the hybrid poplar used for the transformation in this study is an artificial cross between P. alba and P. glandulosa, we found that the NCED3 DNA sequences of these two varieties were significantly similar to that of P. davidiana.…”
Section: Discussionmentioning
confidence: 99%